Application of metal ion doped graphene oxide film in catalytic synthesis of Schiff base
Catalytic through metal ions doped oxygl oxidine graphene membrane, using cation-inate interaction and two-dimensional nano-limited domain channels to solve the problem of high temperature, long-term and low conversion rates of Sterf base in existing technologies, and realized room temperature efficient room temperature Catalytic synthesis, environmentally friendly and friendly.
Patent Information
- Application Number
- CN202411504094.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The prior art faces the problems of high reaction temperature, long reaction time and low room temperature conversion when catalyzing the Schiff base, and the separation of the catalyst and the product is complex, resulting in high production costs and environmental pollution.
Metal ion doped glycene graphene membrane is used as catalytic material, induced reactor orientation through cation-pin-子 采 interaction, and uses a two-dimensional nano-limited domain channel provided by graphene nano tablets to achieve high-efficiency catalytic catalytic catalytic catalytic of the aldosum ketone compounds and amine. synthesis.
At room temperature, the efficient catalytic synthesis of Sififine was achieved. The reaction conversion rate can be up to 100%, and the reaction time is significantly shortened. The energy consumption and operation complexity brought by high temperature heating and long -term reactions is avoided. , Environmental and friendly.
Smart Images

Figure CN119368158A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of membrane catalytic material application and technology, and relates to the application of a metal ion-doped graphene oxide membrane in the catalytic synthesis of Schiff bases, and specifically relates to a graphene oxide membrane catalytic material with adjustable metal ion doping content, a preparation method thereof, and the application of the material in the catalytic synthesis of Schiff bases at high conversion rate at room temperature. Background Art
[0002] Schiff base (also known as Schiff base, Schiff base, Schiff base) is an imine compound with a carbon-nitrogen double bond, which is widely used in organic synthesis, functional dyes, energy catalysis and biomedicine. The literature (J. Supercrit. Fluids 2018, 138, 221-227; Int. J. Org. Chem. 2014, 4, 7-15) reported that the formation mechanism of Schiff base compounds is that the lone pair of electrons of the amino N atom in the primary amine (such as aliphatic amines such as ethylamine or aromatic amines such as aniline) attacks the carbonyl carbon atom in the aldehyde ketone molecule, resulting in a nucleophilic addition reaction to form an α-hydroxyamine intermediate, and then a dehydration reaction generates Schiff base compounds.
[0003] In order to improve the reaction efficiency of Schiff base compounds, at present, the synthesis of Schiff bases generally uses Lewis acids (such as acetic acid, hydrochloric acid, alumina complexes, etc.) or Lewis bases (such as sodium tert-butoxide, sodium hydroxide, etc.) as catalysts (such as Chem. Sci. 2024, 15, 9582-9590; J. Mol. Catal. A. Chem. 2006, 260, 100-4; Tetrahedron: Asymmetry, 2007, 18, 2507-2509 reports). However, since the synthesis reaction of Schiff base is a reversible reaction, it is affected by chemical equilibrium and the reaction still faces some challenges, such as higher reaction temperature (50-150°C), longer reaction time (>2h) and lower reaction conversion rate (50-80%) at room temperature (as reported in Chem.Sci.2024,15,3872-3878; J.Mex.Chem.Soc.2021,65,3,376-395; Adv.Synth.Catal.2023,365,4132-4137). In addition, the process of separating the catalyst from the product is relatively complicated, and the crude product usually needs to be separated and purified by silica gel column chromatography, preparative liquid chromatography or recrystallization. Due to the instability of the imine structure, the decomposition of the Schiff base may occur during the post-treatment process, which increases the production cost, consumes a large amount of reagents, and causes environmental pollution.
[0004] In addition to traditional catalytic methods, microwave synthesis, as a new method for synthesizing Schiff bases, has the advantages of short reaction time and high reaction conversion rate, but it also faces problems such as high preparation cost, poor universality, and high operational risk factor. Summary of the invention
[0005] In order to improve the above technical problems, the present invention provides an application of a metal ion-doped graphene oxide membrane in the catalytic synthesis of Schiff bases.
[0006] According to an embodiment of the present invention, the metal ion doped graphene oxide film comprises a graphene oxide film and metal ions loaded on the surface and interlayers of the graphene oxide film. Preferably, the metal ions are loaded on the surface and interlayers of the graphene film through oxygen-containing groups and graphite domains in the graphene oxide film.
[0007] According to an embodiment of the present invention, the metal ions include main group metal ions and transition metal ions, which may be but are not limited to Li + 、Na + , K + Mg 2+ , Ca 2+ 、Al 3+ , Mn 2+ , Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ and Zn 2+ At least one of .
[0008] According to an embodiment of the present invention, the thickness of the graphene oxide film is, for example, 0.2 to 10 μm, 0.3 to 8 μm, 0.5 to 6 μm, or 0.8 to 2 μm.
[0009] According to an embodiment of the present invention, the interplanar spacing of the metal ion-doped graphene oxide film is between 0.8 and 1.6 nm.
[0010] According to an embodiment of the present invention, in the metal ion-doped graphene oxide film, the mass proportion of metal ions is 0.01-10%.
[0011] According to an embodiment of the present invention, in the metal ion-doped graphene oxide film, the atomic ratio of oxygen to carbon is 0.3 to 0.6.
[0012] According to an embodiment of the present invention, the metal ion-doped graphene oxide film may contain a solvent, such as water.
[0013] According to an embodiment of the present invention, the metal ion-doped graphene oxide film is prepared by reacting a graphene oxide (GO) film with a metal salt.
[0014] According to an embodiment of the present invention, the metal salt includes compounds of main group metal ions and compounds of transition metal ions, which may be but are not limited to LiCl, NaCl, KCl, MgCl2, CaCl2, AlCl3, MnCl2, FeCl3, CoCl2, NiCl2, CuCl2, and ZnCl2.
[0015] In one embodiment of the present invention, the graphene oxide film comprises graphene oxide nanosheets having a layered structure.
[0016] In some embodiments of the present invention, the method for preparing the metal ion-doped graphene oxide film comprises the following steps: 1) assembling the graphene oxide dispersion into a graphene oxide film by vacuum filtration; 2) mixing the graphene oxide (denoted as GO) film with a metal salt solution to obtain a metal ion-doped graphene oxide (denoted as M-GO) film; 3) optionally, heat-treating the film obtained in step 2) to obtain a metal ion-doped graphene oxide (denoted as TM-GO) film.
[0017] In the present invention, by mixing the GO membrane with a metal salt solution, metal ions enter the interlayer of the GO membrane and are fixed through the oxygen-containing groups and graphite domains in the GO membrane.
[0018] According to an embodiment of the present invention, the graphene oxide is a single-layer graphene oxide, and preferably the diameter of the graphene oxide nanosheet is >500nm.
[0019] According to an embodiment of the present invention, the concentration of the graphene oxide dispersion is 0.01 to 2.5 mg / mL, and exemplarily is 0.075 mg / mL.
[0020] In the present invention, in step 1), the graphene oxide dispersion is, for example, a graphene oxide aqueous dispersion. The GO aqueous dispersion is, for example, obtained by mixing GO (such as GO nanosheets) with water, stirring, and ultrasonically dispersing. For example, the stirring time is 10 to 20 minutes, the ultrasonic time is 5 to 15 minutes, and the ultrasonic power is 100 to 300 W, so that the GO nanosheets are uniformly dispersed without destroying the structure of the GO nanosheets.
[0021] In one embodiment of the present invention, the vacuum filtration method is specifically implemented as follows: add the GO aqueous dispersion into a vacuum filtration bottle, start the vacuum pump, and perform vacuum filtration (for example, the vacuum degree of the vacuum filtration is 1 to 5 Pa); as the filtration proceeds, the GO nanosheets in the GO aqueous dispersion are assembled into a layered structure under the action of the water flow, and when the filtration is completed, a GO membrane is obtained.
[0022] According to an embodiment of the present invention, the thickness of the GO membrane is, for example, 0.2 to 10 μm, 0.3 to 8 μm, 0.5 to 6 μm, or 0.8 to 2 μm.
[0023] According to an embodiment of the present invention, the concentration of the metal salt solution is 0.01-1.6 mol / L, preferably 0.5-1.0 mol / L, for example, 0.01 mol / L, 0.1 mol / L, 0.2 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.75 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L.
[0024] According to an embodiment of the present invention, in step 2), the mixing may be immersing the GO membrane in a metal salt solution for a period of, for example, 0.1 h to 60 h, 2 h to 48 h, or 4 to 26 h, exemplified by 4 h, 8 h, or 24 h.
[0025] According to an embodiment of the present invention, step 2) also includes washing and drying the GO membrane mixed with metal ions. For example, the drying is carried out under constant temperature (such as 20-40°C) and constant humidity (such as 5-30% RH), such as in a constant temperature and humidity chamber. Exemplarily, it is allowed to stand at 20-30°C and 10-20% RH for 6-12 hours. The constant temperature and humidity standing treatment can achieve the removal of some free water in the graphene oxide membrane after the filtration is completed.
[0026] According to an embodiment of the present invention, in step 3), the heat treatment time is 4 to 15 hours; the heat treatment temperature is 40 to 180°C, preferably 40 to 100°C, for example, 40°C, 50°C, 60°C, 80°C, 100°C. Heat treatment can promote the dehydration process of the M-GO membrane, thereby regulating the interaction between metal ions and oxygen-containing groups and graphite domains on the surface of GO, enhancing the induction effect of metal ions on reactant molecules, and improving the catalytic effect. Too low a treatment temperature is not conducive to promoting the dehydration process of the M-GO membrane, thereby regulating the interaction between ions and oxygen-containing groups and graphite domains; while too high a treatment temperature will cause the M-GO membrane to thermally decompose, which is not conducive to maintaining the intrinsic chemical structure of the M-GO membrane.
[0027] In one embodiment of the present invention, the method for preparing the metal ion-doped graphene oxide film comprises the following steps:
[0028] 1) dispersing GO in water to obtain a GO aqueous dispersion; assembling the obtained GO aqueous dispersion into a GO membrane by vacuum filtration;
[0029] 2) soaking the GO membrane obtained in step 1) in a metal salt solution, taking it out after soaking and subjecting it to constant temperature and humidity treatment to obtain an M-GO membrane;
[0030] Optionally, 3) the M-GO membrane obtained in step 2) is subjected to heat treatment to obtain a TM-GO membrane.
[0031] According to an embodiment of the present invention, the metal ion-doped graphene oxide film is used as a catalytic material to catalyze aldehydes and ketones and primary amines to generate Schiff bases. For example, the metal ion-doped graphene oxide film is used as a membrane reactor to catalyze aldehydes and ketones and primary amines to generate Schiff bases.
[0032] The present invention also provides a catalytic system, which contains the metal ion-doped graphene oxide film.
[0033] The present invention also provides a method for synthesizing Schiff base by catalysis of metal ion-doped graphene oxide membrane, comprising reacting aldehyde ketone compound with primary amine in the above-mentioned catalytic system to prepare Schiff base compound.
[0034] In the present invention, the product Schiff base will flow out with the mobile phase and leave the catalytic system.
[0035] According to an embodiment of the present invention, the method for synthesizing Schiff base by catalysis of metal ion-doped graphene oxide film comprises the following steps:
[0036] a) dissolving an aldehyde or ketone compound and a primary amine in an organic reagent to obtain a transmembrane reaction solution;
[0037] b) driving the cross-membrane reaction solution through the metal ion-doped graphene oxide membrane in the above-mentioned catalyst system by pressure difference at room temperature to carry out acylation reaction.
[0038] In one embodiment of the present invention, in step a), the molar ratio of the aldehyde and ketone compound to the primary amine is 1:0.9-1.2.
[0039] In one embodiment of the present invention, in step a), the organic solvent is acetonitrile.
[0040] In one embodiment of the present invention, in step a), the concentration of the aldehyde and ketone compounds in the transmembrane reaction solution is 0.01 to 5 mol / L.
[0041] In one embodiment of the present invention, in step b), the reaction time is about 2 to 20 seconds.
[0042] In one embodiment of the present invention, in step b), room temperature refers to a temperature range of 20 to 30°C.
[0043] In one embodiment of the present invention, in step b), the pressure difference is greater than or equal to 0.8 atm.
[0044] In one embodiment of the present invention, in step b), the reaction conversion rate can be up to 100%.
[0045] In one embodiment of the present invention, the aldehyde and ketone compound may be selected from benzaldehyde and 4-methoxybenzaldehyde, for example.
[0046] In one embodiment of the present invention, the primary amine can be selected from aniline, 2-cyanoaniline, 3-cyanoaniline, and 3-nitroaniline, for example.
[0047] Beneficial effects of the present invention:
[0048] (1) The present invention provides a metal ion-doped graphene oxide membrane as a catalytic material for efficient catalytic synthesis of Schiff bases. The metal ion-doped graphene oxide membrane of the present invention retains the inherent acidic catalytic sites of graphene oxide nanosheets while being doped with metal ions that can induce the orientation of reactants through cation-π interactions. At the same time, by regulating the chemical microstructure of the membrane material (such as the type of metal ions, the content of metal ions, and the heat treatment temperature of the membrane material), the catalytic reaction efficiency and reaction selectivity can be effectively improved.
[0049] (2) The metal ions in the metal ion-doped graphene oxide film of the present invention induce the orientation of the reactant molecules through the cation-π interaction, and the confined channels formed between the metal ions and GO make the frontier molecular orbitals of the reactants in the catalytic synthesis of Schiff bases more matched, reducing the molecular freedom, and allowing the molecules to perform bond breaking and bonding reactions in a specific orientation. The molecules are orderly arranged between the layers and flow through the two-dimensional nano-confined channels provided by the graphene oxide nanosheets between the membrane layers, thereby reducing the reaction activation energy and achieving efficient catalytic synthesis of multiple Schiff bases at room temperature.
[0050] (3) The metal ion-doped graphene oxide membrane catalytic material of the present invention retains the inherent acidic catalytic sites of graphene oxide nanosheets, and is also doped with metal ions that can induce the orientation of reactants through cation-π interactions. The two-dimensional nano-confined channels provided by graphene oxide nanosheets between membrane layers and the induced synergistic effect of metal ions on the orientation of reactant molecules are utilized. At the same time, the generated water flows rapidly in the graphite domain in the channel and leaves the reaction system, thereby promoting the forward reaction equilibrium. Combined with the synergistic catalytic effect of the acidic catalytic sites, under the pressure difference drive, through the continuous flow reaction, it shows a higher catalytic efficiency at room temperature, a higher reaction conversion rate (up to 100%), and a significantly shortened reaction time (residence time <20s), avoiding the energy consumption and operational complexity caused by high temperature heating and long-term reaction. This room temperature membrane catalytic system not only simplifies the synthesis steps of Schiff bases, but also significantly improves the purity and yield of the products, providing a new path for efficient and green Schiff base synthesis, and the products do not need to be separated and purified, which is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The present invention is a schematic diagram of the process of preparing the metal ion-doped graphene oxide film catalytic material and catalyzing the Schiff base synthesis reaction;
[0052] Figure 2 Characterization of the structure and catalytic performance of Mg-GO membrane. Figure 2 (A) is the X-ray diffraction (XRD) characterization results of GO membrane (Comparative Example 7) and Mg-GO membrane catalyst materials immersed in different Mg ion concentrations in dry and wet states (the solvent is acetonitrile); Figure 2 Middle (B) is a comparison of the infrared characterization results of the Mg-GO-1.0M membrane of Example 2 and the GO membrane of Comparative Example 7; Figure 2 (C) is the H-NMR spectrum of the Mg-GO membrane material of Example 1; Figure 2 Middle (D) is a comparison of the conversion rates of the Schiff base synthesis catalyzed by metal salt + GO powder (Comparative Example 1), metal salt bulk phase alone (Comparative Example 2), GO powder alone (Comparative Example 3) and Mg-GO film (Example 1). DETAILED DESCRIPTION
[0053] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0054] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0055] In the following examples and comparative examples, unless otherwise specified, "GO dispersion" refers to "graphene oxide dispersion".
[0056] In the following embodiments and comparative examples, unless otherwise specified, "GO film" refers to "graphene oxide film".
[0057] In the following embodiments and comparative examples, unless otherwise specified, "M-GO film" refers to "metal ion-doped graphene oxide film that has not been heat-treated".
[0058] In the following embodiments and comparative examples, unless otherwise specified, "TM-GO film" refers to "metal ion-doped graphene oxide film after heat treatment".
[0059] like Figure 1As shown, first, GO dispersion is assembled into GO membrane by vacuum filtration; then, metal ions are loaded on the surface and interlayer of GO membrane by immersion in metal salt solution to obtain M-GO membrane. By heat treatment, water loss of M-GO membrane is promoted to change the interaction between metal ions and oxygen-containing groups and graphite domains inside GO membrane to obtain TM-GO membrane. By changing the heat treatment temperature, the catalytic performance of metal ion-doped graphene oxide membrane can be optimized.
[0060] The collected liquid through the membrane is quantitatively analyzed by hydrogen nuclear magnetic resonance spectrum to calculate the reaction conversion rate, which specifically includes the following steps:
[0061] Take part of the collected liquid and use deuterated reagent (DMSO) to prepare NMR samples. There are characteristic hydrogen in both the reactant and product molecules. There is a corresponding relationship between the characteristic hydrogen and the number of molecules. The integral area of the single peak at different chemical shifts is compared by single peak fitting calculation, the corresponding molecular number ratio is calculated, and then the reaction conversion rate is calculated, where:
[0062]
[0063] Example 1
[0064] 1) Prepare 0.075 mg / mL GO aqueous dispersion: add 3 mg of GO to 40 mL of deionized water, stir mechanically for 10 min, and disperse by ultrasound (200 W) in an ice water bath for 5 min to obtain a brown transparent solution;
[0065] Prepare 0.01 mol / L MgCl2 solution: weigh 38 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0066] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL of 0.01mol / L MgCl2 solution for 24h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.01M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.01M membrane 2+ The content is 1.4 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.01M membrane in acetonitrile solution is about
[0067] (3) The Mg-GO-0.01M membrane was used as a catalyst to catalyze the reaction of benzaldehyde and aniline to form a Schiff base. The specific operation was as follows: the Mg-GO-0.01M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), purged with nitrogen again, fixed and installed with a sealing gasket to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2mmol benzaldehyde and 2mmol aniline were dissolved in 25mL acetonitrile to prepare the reaction solution, which was prepared as needed; 15mL of the above reaction solution was added above the micro-filtration device, and driven by the pressure difference (~0.9atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.01M membrane reactor, the reactants reacted in the interlayer, and the products flowed out with the acetonitrile solvent; the reaction temperature was 22.3±0.1℃, and the residence time of the reactants was about 7s.
[0068] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 100%.
[0069] Comparative Example 1
[0070] Pre-prepared with Mg 2+ 0.075 mg / mL GO aqueous dispersion: 3 mg of GO was added to 40 mL of deionized water, 14 μL of 0.1 mol / L MgCl2 solution was added thereto, mechanically stirred for 10 min, and ultrasonically dispersed in an ice-water bath (200 W) for 5 min to obtain a brown transparent solution; transferred to a watch glass, placed in a vacuum oven at 25 ° C for vacuum evaporation for 48 h to obtain Mg-GO powder;
[0071] Prepare the reaction solution: dissolve 2 mmol benzaldehyde and 2 mmol aniline in 25 mL acetonitrile to prepare the reaction solution, which is prepared on demand; take 5 mL of the above reaction solution, add the above Mg-GO powder, and keep mechanical stirring; 48 h after the start of the reaction, take 0.5 mL of the sample from the above reaction system, add the deuterated reagent DMSO, and use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated, which was 68%.
[0072] Comparative Example 2
[0073] Prepare the reaction solution: dissolve 2 mmol benzaldehyde and 2 mmol aniline in 25 mL acetonitrile to prepare the reaction solution. Take 5 mL of the above reaction solution, add 0.2 mg MgCl2 solid, keep mechanical stirring, take 0.5 mL of the above reaction solution 48 hours after the start of the reaction, add the deuterated reagent DMSO, and use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 55%.
[0074] Comparative Example 3
[0075] Prepare a 0.075 mg / mL GO aqueous solution in advance: take 3 mg of GO and add it to 40 mL of deionized water, stir mechanically for 10 min, and disperse it by ultrasound (200 W) in an ice water bath for 5 min to obtain a brown transparent solution; transfer it to a watch glass, place it in a vacuum oven at 25 ° C for vacuum evaporation for 48 h to obtain GO powder;
[0076] Prepare the reaction solution: dissolve 2 mmol benzaldehyde and 2 mmol aniline in 25 mL acetonitrile to prepare the reaction solution, which is prepared immediately before use; take 5 mL of the above reaction solution, add the above GO powder, and keep mechanical stirring. 48 hours after the start of the reaction, take 0.5 mL of the sample from the above reaction system, add the deuterated reagent DMSO, and use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated, which was 75%.
[0077] Example 2
[0078] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0079] Prepare 1.0 mol / L MgCl2 solution: weigh 3796 mg MgCl2, add it into 40 mL deionized water, and stir mechanically for 10 min.
[0080] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 1.0mol / L MgCl2 solution for 24h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-1.0M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-1.0M membrane 2+ The content is 17.9 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-1.0M membrane in acetonitrile solution is about
[0081] (3) The Mg-GO-1.0M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to form a Schiff base. The specific operation was as follows: the Mg-GO-1.0M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), purged with nitrogen again, fixed and installed with a sealing gasket to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2mmol 4-methoxybenzaldehyde and 2mmol 2-cyanoaniline were dissolved in 25mL acetonitrile to prepare the reaction solution, which was prepared as needed; 15mL of the above reaction solution was added above the micro-filtration device, and driven by the pressure difference (~0.9atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-1.0M membrane reactor, the reactants reacted in the interlayer, and the products flowed out with the acetonitrile solvent; the reaction temperature was 22.3±0.1℃, and the residence time of the reactants was about 13s.
[0082] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 95%.
[0083] Comparative Example 4
[0084] Pre-prepared with Mg 2+ 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, and 17.9 μL of 1.0 mol / L MgCl2 solution was added thereto. The mixture was mechanically stirred for 10 min, and ultrasonically dispersed in an ice-water bath (200 W) for 5 min to obtain a brown transparent solution. The solution was transferred to a watch glass, and placed in a vacuum oven at 25 °C for vacuum evaporation for 48 h to obtain Mg-GO powder.
[0085] Prepare the reaction solution: dissolve 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-cyanoaniline in 25 mL acetonitrile to prepare the reaction solution, which is prepared on demand; take 5 mL of the above reaction solution, add the above Mg-GO powder, and keep mechanical stirring; 48 h after the start of the reaction, take 0.5 mL of the sample from the above reaction system, add the deuterated reagent DMSO, and use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 7.4%.
[0086] Comparative Example 5
[0087] Prepare a 0.075 mg / mL GO aqueous solution in advance: take 3 mg of GO and add it to 40 mL of deionized water, stir mechanically for 10 min, and disperse it by ultrasound (200 W) in an ice water bath for 5 min to obtain a brown transparent solution; transfer it to a watch glass, place it in a vacuum oven at 25 ° C for vacuum evaporation for 48 h to obtain GO powder;
[0088] Prepare the reaction solution: dissolve 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-cyanoaniline in 25 mL acetonitrile to prepare the reaction solution, which is prepared on demand; take 5 mL of the above reaction solution, add the above GO powder, and keep mechanical stirring; 48 h after the start of the reaction, take 0.5 mL of the sample from the above reaction system, add the deuterated reagent DMSO, and use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated, which was 28%.
[0089] Comparative Example 6
[0090] Prepare the reaction solution: dissolve 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-cyanoaniline in 25 mL acetonitrile to prepare the reaction solution. Take 5 mL of the above reaction solution, add 1.7 mg MgCl2 solid, keep mechanical stirring, take 0.5 mL of the above reaction solution 48 hours after the start of the reaction, add the deuterated reagent DMSO, and use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 7%.
[0091] Comparative Example 7
[0092] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice-water bath (200 W) for 5 min to obtain a brown transparent solution.
[0093] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0°C and 15% RH for 12 hours before being taken out for use. The membrane was named GO membrane. X-ray diffraction data showed that the interlayer spacing of the GO membrane in the acetonitrile solution was approximately
[0094] (3) The GO membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to form a Schiff base. The specific operation was as follows: the GO membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), purged with nitrogen again, fixed and installed with a sealing gasket to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2mmol 4-methoxybenzaldehyde and 2mmol 2-cyanoaniline were dissolved in 25mL acetonitrile to prepare the reaction solution, which was prepared as needed; 15mL of the above reaction solution was added above the micro-filtration device, and driven by the pressure difference (~0.9atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the GO membrane reactor, the reactants reacted in the interlayer, and the products flowed out with the acetonitrile solvent; the reaction temperature was 22.3±0.1℃, and the residence time of the reactants was about 3s.
[0095] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 74%.
[0096] Example 3
[0097] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0098] Prepare 0.9 mol / L MgCl2 solution: weigh 3416 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0099] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 0.9mol / L MgCl2 solution for 24h. After taking it out, rinse the surface with deionized water, place it in a watch glass, and place it in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.9M-24h. Inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that Mg in the Mg-GO-0.9M-24h membrane 2+ The content is 16.1 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.9M-24h membrane in acetonitrile solution is about
[0100] (3) The Mg-GO-0.9M-24h membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to form a Schiff base. The specific operation was as follows: the Mg-GO-0.9M-24h membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in a micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-Cyanoaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a microfiltration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nanoconfined channels of the Mg-GO-0.9M-24h membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 7 s.
[0101] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 95%.
[0102] Example 4
[0103] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0104] Prepare 0.9 mol / L MgCl2 solution: weigh 3416 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0105] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 0.9mol / L MgCl2 solution for 4h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.9M-4h. Inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that Mg in the Mg-GO-0.9M-4h membrane 2+ The content is 16.1 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.9M-4h membrane in acetonitrile solution is about
[0106] (3) The Mg-GO-0.9M-4h membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to form a Schiff base. The specific operation was as follows: the Mg-GO-0.9M-4h membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in a micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-Cyanoaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a micro-filtration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.9M-4h membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 7 s.
[0107] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 95%.
[0108] Example 5
[0109] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0110] Prepare 0.75 mol / L MgCl2 solution: weigh 2847 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0111] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 0.75mol / L MgCl2 solution for 4h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.75M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.75M membrane 2+ The content is 13.6 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.75M membrane in acetonitrile solution is about
[0112] (3) The Mg-GO-0.75M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to generate a Schiff base. The specific operation was as follows: the Mg-GO-0.75M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-Cyanoaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a micro-filtration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.75M membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 8 s.
[0113] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 95%.
[0114] Example 6
[0115] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0116] Prepare 0.5 mol / L MgCl2 solution: weigh 1898 mg MgCl2, add it into 40 mL deionized water, and stir mechanically for 10 min.
[0117] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 0.5mol / L MgCl2 solution for 24h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.5M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.5M membrane 2+ The content is 9.5 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.5M membrane in acetonitrile solution is about
[0118] (3) Mg-GO-0.5M was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to form a Schiff base. The specific operation was as follows: the Mg-GO-0.5M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), purged with nitrogen again, fixed and installed with a sealing gasket to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2mmol 4-methoxybenzaldehyde and 2mmol 2-cyanoaniline were dissolved in 25mL acetonitrile to prepare the reaction solution, which was prepared as needed; 15mL of the above reaction solution was added above the micro-filtration device, and driven by the pressure difference (~0.9atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.5M membrane reactor, the reactants reacted in the interlayer, and the products flowed out with the acetonitrile solvent; the reaction temperature was 22.3±0.1℃, and the residence time of the reactants was about 16s.
[0119] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 95%.
[0120] Example 7
[0121] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0122] Prepare 0.01 mol / L MgCl2 solution: weigh 38 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0123] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL of 0.01mol / L MgCl2 solution for 24h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.01M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.01M membrane 2+ The content is 1.4 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.01M membrane in acetonitrile solution is about
[0124] (3) The Mg-GO-0.01M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 2-cyanoaniline to generate a Schiff base. The specific operation was as follows: the Mg-GO-0.01M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 2-Cyanoaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a micro-filtration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.01M membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 5 s.
[0125] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 75%.
[0126] Example 8
[0127] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0128] Prepare 0.1 mol / L MgCl2 solution: weigh 380 mg MgCl2, add it into 40 mL deionized water, and stir mechanically for 10 min.
[0129] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 0.1mol / L MgCl2 solution for 24h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.1M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.1M membrane 2+ The content is 2.5 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.1M membrane in acetonitrile solution is about
[0130] (3) The Mg-GO-0.1M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and aniline to form a Schiff base. The specific operation was as follows: the Mg-GO-0.1M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), purged with nitrogen again, fixed and installed with a sealing gasket to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2mmol 4-methoxybenzaldehyde and 2mmol aniline were dissolved in 25mL acetonitrile to prepare the reaction solution, which was prepared as needed; 15mL of the above reaction solution was added above the micro-filtration device, and driven by the pressure difference (~0.9atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.1M membrane reactor, the reactants reacted in the interlayer, and the products flowed out with the acetonitrile solvent; the reaction temperature was 22.3±0.1℃, and the residence time of the reactants was about 7s.
[0131] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 100%.
[0132] Example 9
[0133] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0134] Prepare 0.75 mol / L MgCl2 solution: weigh 2847 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0135] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL 0.75mol / L MgCl2 solution for 4h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.75M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.75M membrane 2+ The content is 13.6 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.75M membrane in acetonitrile solution is about
[0136] (3) The Mg-GO-0.75M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 3-cyanoaniline to generate a Schiff base. The specific operation was as follows: the Mg-GO-0.75M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in a micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 3-Cyanoaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a micro-filtration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.75M membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 8 s.
[0137] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 99%.
[0138] Example 10
[0139] 1) Prepare 0.075 mg / mL GO aqueous dispersion: add 3 mg of GO to 40 mL of deionized water, stir mechanically for 10 min, and disperse by ultrasound (200 W) in an ice water bath for 5 min to obtain a brown transparent solution;
[0140] Prepare 0.01 mol / L MgCl2 solution: weigh 38 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0141] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL of 0.01mol / L MgCl2 solution for 24h. After being taken out, the surface was rinsed with deionized water, placed in a watch glass, and placed in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours. After drying, it was taken out for use and named Mg-GO-0.01M. The inductively coupled plasma optical emission spectroscopy (ICP-OES) data showed that the Mg in the Mg-GO-0.01M membrane 2+ The content is 1.4 μmol; X-ray diffraction data show that the interlayer spacing of Mg-GO-0.01M membrane in acetonitrile solution is about
[0142] (3) The Mg-GO-0.01M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 3-nitroaniline to form a Schiff base. The specific operation was as follows: the Mg-GO-0.01M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 3-Nitroaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a micro-filtration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nano-confined channel of the Mg-GO-0.01M membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 8 s.
[0143] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 87%.
[0144] Embodiment 11
[0145] (1) Preparation of 0.075 mg / mL GO aqueous solution: 3 mg of GO was added to 40 mL of deionized water, mechanically stirred for 10 min, and ultrasonically dispersed in an ice water bath (200 W) for 5 min to obtain a brown transparent solution;
[0146] Prepare 0.01 mol / L MgCl2 solution: weigh 38 mg MgCl2, add it to 40 mL deionized water, and stir mechanically for 10 min.
[0147] (2) The GO dispersion prepared above was assembled into a GO membrane by vacuum filtration. After the water on the membrane was drained, the membrane was removed from the filtration device and placed in 10mL of 0.01mol / L MgCl2 solution for 24h. After taking it out, rinse the surface with deionized water, place it in a watch glass, and place it in a constant temperature and humidity chamber at 25.0℃ and 15%RH for 12 hours to obtain Mg-GO-0.01M. The Mg-GO-0.01M membrane was transferred to a vacuum oven at 60℃ for vacuum heat treatment for 12h and then taken out for use. It was named T-Mg-GO-0.01M. The inductively coupled plasma emission spectroscopy (ICP-OES) data showed that the Mg in the T-Mg-GO-0.01M membrane 2+ The content is 1.4 μmol; X-ray diffraction data show that the interlayer spacing of T-Mg-GO-0.01M membrane in acetonitrile solution is about
[0148] (3) The T-Mg-GO-0.01M membrane was used as a catalyst to catalyze the reaction of 4-methoxybenzaldehyde and 3-nitroaniline to form a Schiff base. The specific operation was as follows: the T-Mg-GO-0.01M membrane was purged with nitrogen to remove the dust on the surface, and then the flat and smooth part was selected and cut into a regular octagon (side length 0.8 cm), and then purged with nitrogen again. It was fixed and a sealing gasket was installed to ensure that it was sealed in the micro-filtration device; then the reaction solution was prepared: 2 mmol 4-methoxybenzaldehyde and 2 mmol 3-Nitroaniline was dissolved in 25 mL of acetonitrile to prepare a reaction solution, which was prepared on demand. 15 mL of the reaction solution was added above a micro-filtration device. Driven by a pressure difference (~0.9 atm), the reaction solution passed through the interlayer two-dimensional nano-confined channels of the T-Mg-GO-0.01M membrane reactor, and the reactants reacted in the interlayers, and the products flowed out with the acetonitrile solvent. The reaction temperature was 22.3±0.1°C, and the residence time of the reactants was about 6 s.
[0149] use 1 The components were analyzed by H NMR spectroscopy, and the reaction conversion was calculated to be 98%.
[0150] like Figure 1As shown, the prepared GO dispersion is assembled into a GO membrane by vacuum filtration, and the metal ions are loaded inside the GO membrane by immersion in a metal salt solution to obtain an M-GO membrane. The M-GO membrane is dehydrated by heat treatment to obtain a TM-GO membrane. The M-GO and TM-GO membranes are used as membrane reactors to catalyze aldehydes and ketones and primary amines to form Schiff bases. The reaction solution permeates through the M-GO membrane and the TM-GO membrane under the drive of pressure difference. The intrinsic acidic functional groups of the GO nanosheets and the doped metal ions catalyze the reaction of aldehydes and ketones and primary amines in the confined channels between the membrane layers, and the product Schiff base flows out of the membrane system with the solvent. Specifically, the GO nanosheets provide intrinsic acidic catalytic sites, the nano-confinement between the M-GO membrane and the TM-GO membrane reduces the freedom of the reactant molecules, and the interlayer metal ions induce the orientation of the reactant molecules, enhance their orderliness, and reduce the activation energy of the reaction, thereby greatly improving the efficiency of Schiff base synthesis.
[0151] like Figure 2 As shown in A, the dry interlayer spacing of Mg-GO-0.01M (Example 1), Mg-GO-0.1M (Example 8), and Mg-GO-1.0M (Example 2) obtained by immersion for 24 h and the wet interlayer spacing in acetonitrile solvent show that as the Mg content in the immersion solution increases, the 2+ With the increase of ion concentration, the change of dry-wet interlayer spacing of Mg-GO membrane decreases.
[0152] like Figure 2 As shown in B, 1730cm -1 、1260cm -1 and 1060cm -1 The characteristic absorption peaks at and are the stretching vibrations of the C=O, COC and CO groups on the aromatic rings of graphene oxide. Compared with the GO film of Comparative Example 7, the CO and C=O absorption peak intensities of the Mg-GO film of Example 2 are reduced, which is generally interpreted as evidence of the coordination of the carboxylic acid groups with the metal ions. 2+ After Mg 2+ caused by the ring-opening reaction.
[0153] As shown in Example 1, the ammonolysis reaction of benzaldehyde and aniline was carried out in the Mg-GO-0.01M membrane reactor, and the nuclear magnetic resonance hydrogen spectrum of the product was as follows: Figure 2 As shown in C, the chemical shifts of benzene ring hydrogen are located at 7.94-7.95 (2H) ppm, 7.52-7.55 (3H) ppm, 7.41-7.44 (2H) ppm, 7.25-7.27 (3H) ppm, combined with the characteristic peak at 8.61 ppm in the non-benzene ring region, which corresponds one to one with the product peak; in addition, the characteristic peaks of the reactants benzaldehyde and aniline completely disappear, and the reaction conversion rate is calculated to be 100%.
[0154] The conversion rates of the metal salt + GO powder of Comparative Example 1, the metal salt alone of Comparative Example 2, the GO powder alone of Comparative Example 3, and the Mg-GO film confined catalytic Schiff base synthesis of Example 1 are compared. The results are as follows Figure 2 As shown in (D), it can be seen from the figure that the Schiff base synthesis catalyzed by the Mg-GO-0.01M membrane catalyst achieves rapid (reactant residence time ~7s) and efficient (yield of 100%) material synthesis in the process of directional flow compared with bulk catalysis.
[0155] Compared with Lewis acids such as alumina complexes and sulfuric acid, Lewis bases such as sodium hydroxide and other catalytic materials such as zeolites and molecular sieves, the metal ion-doped graphene oxide membrane catalytic material of the present invention greatly improves the reaction efficiency, shortens the reaction time, and achieves a maximum conversion rate of 100% of Schiff base at room temperature.
[0156] In summary, the present invention provides a (T-)M-GO membrane catalytic material for catalytic synthesis of Schiff bases, and a preparation method and use thereof. The (T-)M-GO membrane catalytic material retains the inherent acidic catalytic sites of graphene oxide nanosheets and is doped with metal ions that can induce the orientation of reactants through cation-π interactions. The two-dimensional nano-confined channels provided by the graphene oxide nanosheets between the membrane layers and the induction effect of the metal ions on the orientation of the reactant molecules are utilized. At the same time, the generated water can flow rapidly in the graphite domain to leave the reaction system and promote the forward reaction equilibrium. Combined with the synergistic catalytic effect of the acidic catalytic sites, the Schiff base is efficiently and rapidly (time <20s) catalytic synthesis is achieved at room temperature (22.3±0.1°C) in a continuous mobile phase reaction driven by pressure difference. The reactant conversion rate can reach up to 100%, and the product does not need to be separated and purified.
[0157] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of metal ion doped graphene oxide membrane in catalytic synthesis of Schiff base.
2. The use according to claim 1, characterized in that The metal ion doped graphene oxide film comprises a graphene oxide film and metal ions loaded on the surface and between layers of the graphene oxide film; Preferably, the metal ions include main group metal ions and transition metal ions, which may be but are not limited to Li + 、Na + , K + Mg 2+ , Ca 2+ 、Al 3+ , Mn 2+ , Fe 3+ 、Co 2+ 、Ni 2+ , Cu 2+ and Zn 2+ At least one of . Preferably, the graphene oxide film has a thickness of 0.2 to 10 μm, preferably 0.8 to 2 μm. Preferably, the interplanar spacing of the metal ion-doped graphene oxide film is between 0.8 and 1.6 nm. Preferably, in the metal ion-doped graphene oxide film, the mass proportion of metal ions is 0.01-10%.
3. The use according to claim 1, characterized in that The metal ion-doped graphene oxide film is prepared by reacting the graphene oxide film with a metal salt. Preferably, the metal salt includes compounds of main group metal ions and compounds of transition metal ions, which may be but are not limited to LiCl, NaCl, KCl, MgCl2, CaCl2, AlCl3, MnCl2, FeCl3, CoCl2, NiCl2, CuCl2, and ZnCl2.
4. The use according to any one of claims 1 to 3, characterized in that: The method for preparing the metal ion-doped graphene oxide film comprises the following steps: 1) assembling the graphene oxide dispersion into the graphene oxide film by vacuum filtration; 2) mixing the graphene oxide film with a metal salt solution to obtain the metal ion-doped graphene oxide film; 3) optionally, heat treating the film obtained in step 2).
5. The use according to claim 4, characterized in that In step 1), the graphene oxide dispersion is a graphene oxide aqueous dispersion; Preferably, the graphene oxide film obtained in step 1) has a thickness of 0.2 to 10 μm.
6. The use according to claim 4, characterized in that In step 2), the concentration of the metal salt solution is 0.01 to 1.6 mol / L, preferably 0.5 to 1.0 mol / L. Preferably, in step 2), the mixing is to immerse the graphene oxide film in a metal salt solution; the immersion time is, for example, 0.1 h to 60 h. Preferably, step 2) further comprises washing and drying the metal ion-doped graphene oxide film obtained after mixing; for example, the drying is carried out under conditions of constant temperature (such as 20-40° C.) and constant humidity (such as 5-30% RH).
7. The use according to claim 4, characterized in that In step 3), the heat treatment time is 4 to 15 hours; the heat treatment temperature is 40 to 180°C.
8. A catalytic system, characterized in that: The invention comprises the metal ion-doped graphene oxide film for use as claimed in any one of claims 1 to 7.
9. A method for synthesizing Schiff base by catalysis of metal ion-doped graphene oxide film, characterized in that: The method comprises reacting an aldehyde or ketone compound with a primary amine in the catalytic system described in claim 8 to prepare a Schiff base compound.
10. The method according to claim 9, characterized in that The steps include: a) dissolving an aldehyde or ketone compound and a primary amine in an organic reagent to obtain a transmembrane reaction solution; b) driving the cross-membrane reaction solution through the metal ion-doped graphene oxide membrane in the above-mentioned catalyst system by pressure difference at room temperature to perform an acylation reaction; The aldehyde and ketone compounds are selected from, for example, benzaldehyde and 4-methoxybenzaldehyde, and the primary amines are selected from, for example, aniline, 2-cyanoaniline, 3-cyanoaniline and 3-nitroaniline.
Citation Information
Patent Citations
Preparing method for non-precious metal ion complexation Schiff base graphene catalyst
CN104993160A
Graphene oxide film with controllable interlayer spacing as well as preparation method and application thereof
CN107640765A
Graphene modified foamed nickel substrate growth copper-based compound catalyst and preparation method thereof
CN113019376A
Metal chelate / graphene oxide composite membrane as well as preparation method and application thereof
CN114618314A
Porous graphene oxide film as well as preparation method and application thereof
CN115364696A
Cited By
Application of metal ion doped graphene oxide membrane catalytic material in synthesis of sulfone by catalyzing thioether oxidation reaction
CN120058570A
Use of a metal ion-doped graphene oxide membrane catalytic material in catalyzing sulfide oxidation reaction to synthesize sulfone
CN120058570B
Application of transition metal ion doped graphene oxide membrane catalytic material in synthesis of 4-phenylmorpholine antibacterial derivative
CN122355965A
Use of a transition metal ion-doped graphene oxide film catalytic material in synthesis of 4-phenylmorpholine antibacterial derivatives
CN122355965B